Big Five personality traits and sex - Uwe Jirjahn; Martha Ottenbacher (Journal of Population Economics, 2022)
Sexual well-being plays an important role in the quality of life. Against this background, we provide an economics-based approach to the relationship between the Big Five personality traits and various dimensions of sexuality. From a theoretical viewpoint, personality influences sexual well-being not only by how a person feels about sex, but also by how the person behaves in a sexual relationship. Personality shapes information sharing about sexual preferences, the way dissonant sexual preferences of the partners are handled, and the extent to which a person is committed to promises made to a partner. Using a large representative dataset from Germany, we find that personality traits play a role in a person's own sexual satisfaction, in (the self-assessment of) fulfilling their partner's sexual needs and desires, in sexual communication, in actual and desired frequency of sex, and in extradyadic affairs. Conscientiousness contributes to a mutually beneficial sex life and increases a person's commitment to their partner. The opposite holds true for neuroticism. While extraversion and openness to experience help realize a mutually beneficial sex life, we find no evidence that they have a commitment value. On the contrary, extraversion is associated with lower commitment to the partner. Agreeableness contributes to higher commitment. However, agreeableness appears to make people more reluctant to express their sexual needs and desires.
Keywords: D10; D91; J10; J12; 330; Big Five personality traits; Sexual satisfaction; Frequency of intercourse; Sexual infidelity; Sexual communication; Family economics